DEVELOPMENT AND ASSESSMENT OF FREE-FLOW SPEED MODELS BASED ON DIFFERENT METHODS OF MEASUREMENTS FOR INTER URBAN MULTILANE HIGHWAYS IN MALAYSIA - Leong, Lee Vien; Azai, Tuti Azmalia; Goh, Wins Cott; Mohd Shafie, Shafida Azwina (Journal of Applied Engineering Science, 2019)
This study aims to assess and compare several free-flow speed measurement methods that are suitable for Malaysian multilane highways. Free-flow speed is defined as a speed where the driver can maintain their own desired speed without obstruction or without being influenced by other road users. Data collection was conducted at 16 sites across Peninsular Malaysia during peak and off-peak periods. The measurement methods use different criteria which includes linear speed-density relationship graphs, the average speed of vehicles recorded during low to moderate traffic volume and also the average speed of vehicles with a pre-determined headway. Subsequent analysis was conducted and compared by performing multiple regression analyses. Results indicate that measurement of free-flow speed based on pre-determined headway is the best-suited model for Malaysian multilane highways. The model was determined as the best fit due to its highest R value of 0.954 and the highest score of 12/15 for the performance indicator analysis. These findings can greatly contribute to traffic engineers of Malaysia in determining a more precise free-flow speed for the design and operational assessment of multilane highways in Malaysia.